Perancangan Mobile Ad-Hoc Network Mengunakan Optimasi Routing AOMDV - Aditya Wijayanto; Alon Jala Tirta Segara; Faisal Dharma Adhinata (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Natural disasters are unpredictable events of the time and place that occur. In fact, natural disasters in Indonesia often make the destruction of an area that can cause the destruction of facilities in the region. Disaster events make regional communication usually cut off, so it requires backup communication tools in the event of a disaster. Backup communications can be built using infrastructure without a network. In this research we will design a network system where we will try to use the system to select some good ad hoc mobile protocols for sending data. The movement of each node means that each node is the data sent. The proposed service may also provide such services. . However, since there is no access to banks in disaster areas, the use of electronic currency for online transactions has become limited. Therefore, the secure payment system will be centered on our offline transactions after conducting simulations and looking at the existing comparison values then we get a conclusion about the results of the parameter trial in the end to end delay test parameters in this simulation we also get the best value that on node 50 is 3.2 seconds and on node 30 get a value of 15.03 seconds this happens because there is a 50